Factors Associated with Resilience Family Caregiver of Patients with Dementia - Rohayati, Rohayati; Pradana, Anung Ahadi (STIKep PPNI Jawa Barat, 2025)
Aims: Dementia represents a critical public health issue. Family caregivers play a vital role in providing care due to limited healthcare resources, yet they face significant bio-psycho-social challenges that impact their resilience. Understanding the factors influencing caregiver resilience is crucial for developing targeted interventions. Objective: This study aimed to analyze factors associated with the resilience of family caregivers of PwD in Bekasi City, Indonesia. Methods: A cross-sectional study was conducted among 42 family caregivers of PwD. Resilience was measured using the Connor-Davidson Resilience Scale (CD-RISC). Descriptive and bivariate analyses were performed to examine associations between demographic characteristics, caregiving duration, dementia knowledge, and resilience. Results: The majority of caregivers were female (71.4%), aged 18–59 years (83.3%), and unemployed (71.4%). Most caregivers had a moderate level of resilience (71.4%), while 28.6% demonstrated high resilience. Bivariate analysis showed no significant associations between resilience and demographic factors, including gender, age, education level, employment status, caregiving duration, and dementia-related knowledge (p > 0.05). Conclusion: Resilience among caregivers is not significantly influenced by demographic variables, highlighting the importance of focusing on psychosocial and environmental factors to strengthen resilience. Future efforts should prioritize community-based interventions, stress management programs, and social support systems to enhance the well-being of caregivers and the quality of care for PwD.